Free Choice Feeding on the Quality of Quail Eggs (Coturnix coturnix-japonica) - Eva Morani Silaban; Ma'ruf Tafsin; Nevy Diana Hanafi (Talenta Publisher, 2019)
Quail is one of the potential sources of animal protein from poultry as egg producers. An egg contains complete nutrients, namely protein, fat, vitamins, and minerals. As food, eggs must be maintained both physically and chemically to be safe for consumption. This study aimeds to examine the effect of selective feeding on the quality of quail eggs. This research was carried out at Percut Sei Tuan Subdistrict, Deli Serdang Regency, North Sumatra, which had been implemented from August to November in 2018. The study used a completely randomized design with 4 treatments and 5 plots. The study used egg samples from quail aged five (5) months. The treatment consists of Commercial feed (T0), 2 energy source feed (rice bran, corn) with 2 (T1), 3 (T2), 4 (T3) protein source feeds (fish meal, soybean meal, coconut meal, Poultry Meat Meal). The results showed that the treatment gave a significant effect (P<0.05) on egg weight, albumen, and eggshell weight, commercial feed showed eggs weight higher than free choice feeding treatments, while among free choice feeding treatment did not show significant effect. The free choice feeding treatment has a significant effect on the yolk weight, where T2 has the lowest yield. Percentage of yolk, albumen, quail eggshell and egg index, egg yolk index, albumen index, haugh unit and quail yolk color did not show significantly different (P>0.05) among treatment. It can be concluded that the commercial feed showed higher egg weight but had no significant effect (P>0.05) on the proportion of eggs and the interior quality of quail eggs, while among free choicee feeding treatment has no effect.